Analisis Pelaksanaan Pekerjaan Pondasi Bored Pile Pada Proyek Pembangunan Apartemen Monde City - Jali, Allan; Wibowo, Petrus Haryanto (Jurnal Ilmiah Rekayasa Sipil, 2023)
The foundation is a very important structural element in a building. The bearing capacity of the soil is a foundation support, where a foundation is defined as an underground building that transmits the load originating from the weight of the building itself and the loads acting on the building to the surrounding soil. This study aims to determine the bearing capacity of the bored pile foundation in the Monde City Batam Apartment development project. The research method for implementing bored pile work was carried out by the Monde City Batam Apartment development project which is located at the address of Sadai Village, Bengkong District, Batam City, Riau Islands. Based on the results of a comparison of digging the ground for bored pile installation in the monde city Apartment, it can be concluded that the heavy equipment used is the Auger and Bucket with the results of the data that have been obtained that drilling using an Auger drill which takes 3 hour and 01 minutes is the fastest option for digging the soil layer to be used for installation of bored piles.